The case of diagnosis of imported cutaneous leishmaniasis in Zaporozhye - Savelyev, V. G.; Firulina, O. M; Ryabokon, E. V.; Zarudna, O. V.; Dobryak, T. Yu.; Gostisheva, O. I.; Furyk, E. A.; Zadiraka, D. A. (Zaporozhye Medical Journal, 2014)
Aim. Article presents the current data on the clinical and epidemiological issue of leishmaniasis. Methods and results. Leishmaniasis is endemic disease in 88 countries, mainly in tropical and subtropical climates. Probability of importation of American cutaneous leishmaniasis in our country is practically zero, but, given the rarity of this disease, we present own clinical observation of imported cutaneous leishmaniasis in Zaporozhye. At the beginning of the third millennium has greatly increased the urgency of tropical parasitic diseases, including leishmaniasis. According to WHO, the world’s 14 million people are infected each year there is about 2 million new cases and about 350 million live in areas at risk. Leishmaniasis - a group of vector-borne protozoal disease in humans and animals characterized by lesions of the internal organs (visceral leishmaniasis) or the skin and mucous membranes (cutaneous leishmaniasis), which is the vector mosquitoes. We present their own clinical observations of American cutaneous leishmaniasis imported. Patient S., 41 years was hospitalized in Zaporozhye Regional Clinical Hospital infectious on 07.17.2013, with suspected cutaneous leishmaniasis. From the history of the disease is known that for the first time in February 2013 the patient have got relative to blade area redness and bump that appeared above the skin, and had a magnitude of 2,3 mm brownish-red. To the doctor the patient has not addressed. After 1,5-2 months bump grew and he began to stand out ichor, which dries and formed a crust on top of the hump. Further small ulcers that did not bring discomfort and pain to the patient appeared. However, every month ulcer increased. In July, after vacation at sea, rose weeping sores and perifocal inflammation appeared. Ulcer size reached 2 cm in diameter. The patient first applied to the dermatologist at the beginning of July 2013. Dermatologist excluded secondary syphilis and tuberculosis skin and sent to an infectious diseases doctor with suspected cutaneous leishmaniasis (Mexican?). The patient was admitted to the department number 1 in Zaporizhzhya Regional Infectious Hospital. From the epidemiological history it was known that in December 2012 the patient was in Mexico, in its southeastern part. Tours visited the waterfall, located in the jungle. By the waterfall he was in a bathing suit and does not exclude the bites of mosquitoes. Objective status on admission: no complains. Local Status: In a field of ulcerative blade element 2 cm in diameter, covered with dry serous crust with a raised edge. Ulcerative element palpation painless. On the periphery of the ulcer there were inflammatory small roller, moderately thick, smooth. Perifocal inflammation of about 0,5 cm in removing the crusts revealed crater hole, the bottom close-grained, ulcer edges are rough, eroded occurred granulation. Discharge from the ulcers were scarce, sero-purulent character turned into a drying brownish crust. To confirm the diagnosis of leishmaniasis patient passed tests. The prepared area for scraping was anesthetize, then the end of the scalpel scrape small pieces of tissue, while scraping with sanious liquid is transferred to a glass slide, fixed and stained by the Romanovsky- Himze. So after taking clarify technical characteristics of the material for this specific study was conducted repeated studies that included biopsies of ulcerative item. Ultimately, the only element of ulcer biopsy taken on the periphery of the ulcer site with regional infiltration at the site of fresh granulation, gave a positive result. In preparation pathogen was detected - Leishmania sp., Amastihotna form. Conclusion: The clinical observation demonstrates the case of importation to Ukraine rather exotic disease - cutaneous leishmaniasis. This case should alert healthcare workers about the possibility of re-importation of cases of this disease in our country, which requires mandatory specific confirmation of the diagnosis, which is possible only with some technical features of the study material.